2015
DOI: 10.1186/s12974-015-0384-7
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation induces antiapoptotic and anti-inflammatory effects in epileptic rats

Abstract: BackgroundStatus epilepticus (SE) is a severe condition that may lead to hippocampal cell loss and epileptogenesis. Some of the mechanisms associated with SE-induced cell death are excitotoxicity, neuroinflammation, and apoptosis.ObjectiveThe objective of the present study is to test the hypothesis that DBS has anti-inflammatory and antiapoptotic effects when applied during SE.MethodsRats undergoing pilocarpine-induced SE were treated with anterior thalamic nucleus (AN) deep brain stimulation (DBS). Inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 27 publications
6
22
0
Order By: Relevance
“…In recent years, DBS has been considered to be a successful treatment for epileptic patients who are deemed to be clinically refractory and are not candidates for surgical resection. We recently found that ANT DBS delivered during pilocarpine‐induced SE had antiapoptotic and anti‐inflammatory effects on the hippocampus . In the present study, we found that this treatment reduced hippocampal cell loss in different subfields, although it did not significantly influence memory performance.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…In recent years, DBS has been considered to be a successful treatment for epileptic patients who are deemed to be clinically refractory and are not candidates for surgical resection. We recently found that ANT DBS delivered during pilocarpine‐induced SE had antiapoptotic and anti‐inflammatory effects on the hippocampus . In the present study, we found that this treatment reduced hippocampal cell loss in different subfields, although it did not significantly influence memory performance.…”
Section: Discussionsupporting
confidence: 49%
“…In the PDBSs group, stimulation was given during the six hour following SE onset (as in the PDBSa group) and also during the silent phase (20 days), administered for 6 h/day at 130 Hz, 90 μsec, and 200 µA. These setting were chosen because they were effective in our previous studies, while higher current has neuroprotective effects in the acute phase , in the chronic phase, the lower current results in seizure reduction . Control rats did not have implanted electrodes ( n = 37, PCTL group and n = 11, CTL group).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that STN-DBS was able to decrease IL-6 expression in epileptic rats (Amorim et al 2015;Chen et al 2017). We found that IL-6 protein levels are significantly downregulated in the GP following 6-OHDA, when compared to saline-injected control rats.…”
Section: Discussionsupporting
confidence: 48%
“…However, in their A1 polarization state, the inflammatory phenotype inhibits the glutamate reuptake transporters altering the formation and quality of new synapses (Korn et al 2005;Liddelow et al 2017); hence, controlling inflammation is essential to regulate the synapses disruption. The role of DBS in reducing hippocampal neuroinflammation in epileptic rats has been previously described (Amorim et al 2015), and the importance of astrocytes in response to stimulation has been discussed (Fenoy et al 2014), but not yet tested. We postulated that DBS/HFS modulates classical inflammatory activation of astrocytes, contributing to the overall control of neuroinflammation in PD.…”
Section: Introductionmentioning
confidence: 99%